2010
DOI: 10.3389/fnhum.2010.00059
|View full text |Cite
|
Sign up to set email alerts
|

What physiological changes and cerebral traces tell us about adhesion to fiction during theater-watching?

Abstract: Live theater is typically designed to alter the state of mind of the audience. Indeed, the perceptual inputs issuing from a live theatrical performance are intended to represent something else, and the actions, emphasized by the writing and staging, are the key prompting the adhesion of viewers to fiction, i.e., their belief that it is real. This phenomenon raises the issue of the cognitive processes governing access to a fictional reality during live theater and of their cerebral underpinnings. To get insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
2
11
0
5
Order By: Relevance
“…Most of these features may relate to changes in regional brain activity and in functional connectivity between brain regions (Maquet et al, 2005; Massimini et al, 2010). The ability of the brain to accept a fictional reality it creates as an actual one (adhesion), and thus alter the state of its own perception, is related to activations of the left ventral inferior frontal gyrus and left posterior superior temporal sulcus (Metz-Lutz et al, 2010). Interestingly enough, both regions display increased activity during sleep compared to wakefulness (Braun et al, 1997; Dehaene-Lambertz et al, 2002; Kaufmann et al, 2006).…”
Section: The Dreaming Brain As An “Endogenous” Morel's Machine and Itmentioning
confidence: 99%
“…Most of these features may relate to changes in regional brain activity and in functional connectivity between brain regions (Maquet et al, 2005; Massimini et al, 2010). The ability of the brain to accept a fictional reality it creates as an actual one (adhesion), and thus alter the state of its own perception, is related to activations of the left ventral inferior frontal gyrus and left posterior superior temporal sulcus (Metz-Lutz et al, 2010). Interestingly enough, both regions display increased activity during sleep compared to wakefulness (Braun et al, 1997; Dehaene-Lambertz et al, 2002; Kaufmann et al, 2006).…”
Section: The Dreaming Brain As An “Endogenous” Morel's Machine and Itmentioning
confidence: 99%
“…Il a été montré que l'adhésion à une réalité fictionnelle est très dépendante de l'intention du metteur en scène (Bressan, 2012;Metz-Lutz et al, 2010). Il convient donc que le CM intègre de manière claire et repérable l'intention de l'éducateur de faire adhérer les étudiants.…”
Section: L'intervention éDucativeunclassified
“…L'adhésion sera confirmée s'il y a convergence des événements subjectifs et des variations du rythme cardiaque avec au moins deux messages mis en scène. Les zones cérébrales activées seront identifiées et comparées à celles décrites par Metz-Lutz et al (2010).…”
Section: Expérience 2: Irmf + Ecg + Entretiensunclassified
See 1 more Smart Citation
“…A handful of neuroscientific works have explored the neural underpinning of the distinction between real and fictional events. These studies reported that appraising an event as fictional engaged the lateral prefrontal cortex and anterior cingulate cortex (Abraham, von Cramon, & Schubotz, 2008;Altmann, Bohrn, Lubrich, Menninghaus, & Jacobs, 2012;Metz-Lutz, Bressan, Heider, & Otzenberger, 2010), involved in cognitive control and ER (Ochsner & Gross, 2005;Ochsner, Silvers, & Buhle, 2012). On the other hand, reality engaged, to a greater extent, the cortical midline structures (Abraham et al, 2008;Han, Jiang, Humphreys, Zhou, & Cai, 2005;Hsu, Conrad, & Jacobs, 2014), known to be involved in autobiographical memory and self-referential processing (Martinelli, Sperduti, & Piolino, 2013;Northoff, 2005).…”
mentioning
confidence: 99%